Emerging Delivery Strategies of Carbon Monoxide for Therapeutic Applications: from CO Gas to CO Releasing Nanomaterials. Issue 49 (30th October 2019) - Yan, Haili; Du, Jiangfeng; Zhu, Shuang; Nie, Guangjun; Zhang, Hui; Gu, Zhanjun; Zhao, Yuliang
Abstract: Carbon monoxide (CO) therapy has emerged as a hot topic under exploration in the field of gas therapy as it shows the promise of treating various diseases. Due to the gaseous property and the high affinity for human hemoglobin, the main challenges of administrating medicinal CO are the lack of target selectivity as well as the toxic profile at relatively high concentrations. Although abundant CO releasing molecules (CORMs) with the capacity to deliver CO in biological systems have been developed, several disadvantages related to CORMs, including random diffusion, poor solubility, potential toxicity, and lack of on‐demand CO release in deep tissue, still confine their practical use. Recently, the advent of versatile nanomedicine has provided a promising chance for improving the properties of naked CORMs and simultaneously realizing the therapeutic applications of CO. This review presents a brief summarization of the emerging delivery strategies of CO based on nanomaterials for therapeutic application. First, an introduction covering the therapeutic roles of CO and several frequently used CORMs is provided. Then, recent advancements in the synthesis and application of versatile CO releasing nanomaterials are elaborated. Finally, the current challenges and future directions of these important delivery strategies are proposed. Abstract : This review covers the recent advancement of nanomaterial‐based strategies for CO delivery. It starts with a brief introduction of CO therapeutic roles and several typical CO‐releasing molecules. Next, recent advances in the synthesis and application of CO‐releasing nanomaterials are highlighted. Lastly, the current challenges and future directions of this promising field are proposed.